Fluorescence redistribution after photobleaching. A new multipoint analysis of membrane translational dynamics. - Koppel, D E (1979)
A theoretical formulation and experimental methodology are presented for a new multipoint analysis of membrane translational dynamics. The redistribution of fluorescent probe after a localized photobleaching pulse is monitored at several locations by a focused laser beam sequentially scanned through the bleached area. The spatial information so obtained provides a unique sensitivity to possible systematic flow and a direct internal calibration of the characteristic transport distance. These capabilities are demonstrated with experimental data on a reconstituted multibilayer system.